Echocardiographic study of early left ventricular remodeling in highly trained preadolescent footballers - Zdravkovic, M.; Perunicic, J.; Krotin, M.; Ristic, M.; Vukomanovic, V.; Soldatovic, I.; Zdravkovic, D. (Journal of Science and Medicine in Sport, 2010)
Almost all the studies of athlete's heart have been carried out on adult and older adolescent players; hence the limited data on the cardiac response to exercise in the beginning of the active sports career in the youngest athletes. The study was designed to examine the physiological limits of left ventricle (LV) cavity size and wall thickness in elite footballers at the preadolescent age, it the beginning of the active sports career. Ninety-four highly trained male footballers (mean aged 12.85 ± 0.84) competing in the Serbian Football League and 47 age-matched healthy male controls, aged 12-14, were enrolled in the study. All the echocardiographic findings were adjusted to BSA-0.5, while left ventricle mass (LVM) was additionally adjusted to BSA-1.5. Reference ranges were defined as values of 5-95th centile according to the mean values in both groups. The proportions of the footballers with LV dimensions outside expected ranges were additionally noted. The data indicate significant increases in absolute values of LV dimensions, aortic root size and left atrium (p < 0.001) in preadolescent professional footballers compared with the values expected for age-matched controls, whereas there are no differences in absolute values of ventricular septal and posterior wall thickness, LV wall thickness and LVM (p > 0.05). Upon body-size adjustments, significant increases were observed in all echocardiographic parameters (p < 0.001). Our data indicate an early cardiac remodeling, already apparent in preadolescence, even after a short period of training.